2018
DOI: 10.3390/su10103422
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Positive Resources of Workers for Sustainable Development: Is Emotional Intelligence a Mediator for Optimism and Hope?

Abstract: The 21st century is characterized by unpredictable and changing environments that require individuals and organizations to adapt to these challenges and prepare for continuous transitions in the work environment. Optimism and hope are positive resources that are key factors in navigating this post-modern work scenario. Emotional intelligence can be considered as another important variable in this context and furthermore, research has shown it can be increased through specific training. The aim of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 39 publications
5
46
0
3
Order By: Relevance
“…Finally, as we expected, H3 found its confirmation since in 20 out of 20 models, emotional intelligence acted as a mediator in the relationship between different dimensions of temperaments and the sense of coherence. These results are consistent with earlier studies [67] that reported a mediatory role of EI between some personality traits and positive resources. Such a mediatory effect may be because EI allows monitoring and management of one's own emotions to guide one's thinking and actions [68].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, as we expected, H3 found its confirmation since in 20 out of 20 models, emotional intelligence acted as a mediator in the relationship between different dimensions of temperaments and the sense of coherence. These results are consistent with earlier studies [67] that reported a mediatory role of EI between some personality traits and positive resources. Such a mediatory effect may be because EI allows monitoring and management of one's own emotions to guide one's thinking and actions [68].…”
Section: Discussionsupporting
confidence: 93%
“…Emotional stability is a major psychological characteristic that is generated when people encounter difficulties or stress in daily life, and it has a stabilizing effect [24,34]. Furthermore, it is one of the big five personality traits proposed by McCrae and Costa [35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible to envisage that the most emotionally intelligent people who are satisfied in the need for relatedness display higher levels of individual well-being. In supporting this view, the mediation role of emotional intelligence in the relationship between personal traits and positive resources predicting individual well-being has recently been observed [42]. Moreover, the finding that emotional intelligence is related to the need for relatedness factor of SDT adds new light on the relationship between motivational systems and emotional intelligence [66,67].…”
Section: Discussionmentioning
confidence: 92%
“…Recent results indicated that emotional intelligence mediates the relationship between personality traits and both hope and optimism, suggesting that stable factors and positive outcomes might be modulated through the mediation role of emotional intelligence [42]. The role of individual differences on the strength of implicit motives in the relationship between needs for relatedness and well-being has also been observed [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation